Collaborative Art Project III - Workshop: Geography of colour - Antoniou, Klitsa (My University, 2026)
Collaborative Art Project III Lecture: Lines and Treads 14.11.22 11:00 Workshop: Geography of colour 16/11/22 10:00-14:00 Dr Natacha Antão Moutinho Professor of Drawing Minho University, Portugal